2000
DOI: 10.1128/aem.66.7.3110-3112.2000
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Fe Superoxide Dismutase and Catalase in Resistance of Campylobacter coli to Freeze-Thaw Stress

Abstract: We demonstrated that oxidative stress plays a role in freeze-thaw-induced killing of Campylobacter coli following analysis of mutants deficient in key antioxidant functions. Superoxide anions, but not H 2 O 2 , were formed during the freeze-thaw process. However, a failure to detoxify superoxide anions may lead to spontaneous disproportionation of the radicals to H 2 O 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 14 publications
2
48
1
1
Order By: Relevance
“…Our results suggest that the observed loss of viability reflected mostly death of cells in response to freezing and/or thawing (and depended less on the length of the frozen storage). Recent work with Campylobacter coli also showed similar sensitivity to freezing and thawing and identified the major role of superoxide anions in freeze-thawing injury (27). It is not yet known whether oxidative damage is implicated in cold tolerance of C. jejuni (or C. coli).…”
Section: Discussionmentioning
confidence: 97%
“…Our results suggest that the observed loss of viability reflected mostly death of cells in response to freezing and/or thawing (and depended less on the length of the frozen storage). Recent work with Campylobacter coli also showed similar sensitivity to freezing and thawing and identified the major role of superoxide anions in freeze-thawing injury (27). It is not yet known whether oxidative damage is implicated in cold tolerance of C. jejuni (or C. coli).…”
Section: Discussionmentioning
confidence: 97%
“…The AhpC protein catalyzes the reduction of alkyl hydroperoxide to alcohols (30). Previous reports have shown that AhpC and SodB are required for C. jejuni survival in aerobic conditions and that a C. jejuni katA mutant is affected in its ability to survive within macrophages (3,9,30,39). The Tpx protein exhibits high homology with antioxidant enzymes from other bacteria, but its role in oxidative stress defense in C. jejuni requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, C. jejuni proteins involved in responding to aerobic stress have also been identified. SodB and KatA have been shown to counteract the detrimental effects of aerobic stress (69). The heat shock protease HtrA and the regulator HspR have been shown to be important for short-term aerobic tolerance (3,12).…”
mentioning
confidence: 99%